2015
DOI: 10.1093/humrep/dev192
|View full text |Cite
|
Sign up to set email alerts
|

Only a minority of sex chromosome abnormalities are detected by a national prenatal screening program for Down syndrome

Abstract: This study received support from Aarhus University and the Novo Nordisk Foundation. The authors have no competing interests that may be relevant to the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 41 publications
5
37
1
Order By: Relevance
“…In the current study, we observed that KS‐GCT cases did not differ significantly from the non–KS‐GCT cases with respect to birthweight. Viuff et al did not find a difference in birthweight between KS cases and non‐KS cases, suggesting that KS does not impact birthweight …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the current study, we observed that KS‐GCT cases did not differ significantly from the non–KS‐GCT cases with respect to birthweight. Viuff et al did not find a difference in birthweight between KS cases and non‐KS cases, suggesting that KS does not impact birthweight …”
Section: Discussionsupporting
confidence: 83%
“…As others have reported, we observed a higher, although nonsignificant, percentage of KS‐GCT males born to mothers of older age . There are 2 reports of an increased risk of KS for each decade increase in paternal age (controlling for maternal age); however, we did not observe a difference in paternal age between case groups.…”
Section: Discussioncontrasting
confidence: 67%
“…Yet, some spontaneous abortions with T18 or T13 might not be captured by our surveillance system due to the lack of karyotype analysis. The incidence of sex chromosomal abnormalities was 1% in pregnancies when prenatal diagnosis was performed, with prenatal detection rate below 50% [4, 25]. The fact that newborns without clinics presentation might not have undergone karyotype confirmation even if they possessed sex chromosomal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Other ultrasound findings suggestive of TS are coarctation of the aorta and/or left-sided cardiac defects (which should be further imaged by fetal echocardiography), brachycephaly, renal anomalies, polyhydramnios, oligohydramnios and growth retardation (40). Abnormal triple or quadruple maternal serum screening (alpha-fetoprotein, human chorionic gonadotropin, inhibin A and unconjugated estriol) may also suggest the diagnosis of TS (41), but these tests may be perfectly normal together with normal nuchal fold thickness (42). Ultrasound and maternal serum screening are not diagnostic, and karyotype confirmation of TS is obligatory.…”
Section: Prenatal Diagnosismentioning
confidence: 99%